Revision der paläarktischen Yponomeutidae unter besonderer Berücksichtigung der Genitalien (Lepidoptera). - Friese, Gerrit (Contributions to Entomology = Beiträge zur Entomologie, 1960)
Investigations under discussion have proved the family Yponomeutidae s. 1. being a heterogenous complex od several families and some genera of different or still quite dubious position. There is given a revision of the palaearctic species of the family Yponomeutidae s. str. as a result of investigations on male and female genitalia, external characters and geographic distribution of the adults as like as larval morphology and food plant preference. There remain disregarded the Plutellidae, the hitherto subfamily Argyresthiinae to which family rank is due and several genera the systematic position of which as not belonging to these three families is discussed. There are described as new 5 genera and 8 species. 5 genera and 12 species were found falling into synonymy. Nomenclatural Acts ildefonsella Friese, 1960 (Banghaasia), spec. n. dealbatella Zeller, 1847 (Calantica), syn. n. of Niphonympha albella (Zeller, 1847) albithoracellus Gaj, 1954 (Euhyponomeutoides), syn. n. of Kessleria rufella (Tengström, 1848) nigrifimbriatus Christoph, 1882 (Hyponomeuta), syn. n. of Yponomeuta plumbellus (Denis & Schiffermüller, 1775) albanica Friese, 1960 (Kessleria), spec. n. caucasica Friese, 1960 (Kessleria), spec. n. longipenella Friese, 1960 (Kessleria), spec. n. pyrenaea Friese, 1960 (Kessleria), spec. n. tatrica Friese, 1960 (Kessleria), spec. n. ribesiella (de Joannis, 1900) (Nordmaniana), comb. n. hitherto Zelleria ribesiella de Joannis, 1900 passerella Zetterstedt, 1840 (Oecophora), syn. n. of Swammerdamia pyrella (de Villers, 1789) restrictellus Chrétien, 1915 (Paradoxus), syn. n. of Zelleria oleastrella (Millière, 1864) caesiella (Hübner, 1810) (Paraswammerdamia), comb. n. hitherto Tinea caesiella Hübner, 1810 conspersella (Tengström, 1848) (Paraswammerdamia), comb. n. hitherto Tinea conspersella Tengström, 1848 iranella Friese, 1960 (Paraswammerdamia), spec. n. lapponica (Petersen, 1932) (Paraswammerdamia), comb. n. hitherto Swammerdamia lapponica Petersen, 1932 lutarea (Haworth, 1828) (Paraswammerdamia), comb. n. hitherto Erminea lutarea Haworth, 1828 ornichella Friese, 1960 (Paraswammerdamia), spec. n. anas (Stringer, 1930) (Pseudocalantica), comb. n. hitherto Niphonympha anas Sgtringer, 1930 combinella (Hübner, 1786) (Pseudoswammerdamia), comb. n. hitherto Tinea combinella Hübner, 1786 cagnatella Treitschke, 1832 (Tinea), syn. n. of Yponomeuta padellus (Linnaeus, 1758) rorella Hübner, 1796 (Tinea), syn. n. of Yponomeuta padellus (Linnaeus, 1758) scambota Meyrick, 1928 (Xyrosaris), syn. n. of Zelleria oleastrella (Millière, 1864) bakeri Walsingham, 1894 (Yponomeuta), syn. n. of Kessleria egregiella (Duponchel, 1838) polysticta Butler, 1879 (Yponomeuta), syn. n. of Yponomeuta polystigmellus Felder, 1862 Banghaasia Friese, 1960 (Yponomeutidae), gen. n. Eucedestis Paclt, 1951 (Yponomeutidae), syn. n. of Cedestis Zeller, 1839 Euhyponomeutoides Gaj, 1954 (Yponomeutidae), syn. n. of Kessleria Nowicki, 1864 Hofmannia Wocke, 1877 (Yponomeutidae), syn. n. of Kessleria Nowicki, 1864 Nordmaniana Friese, 1960 (Yponomeutidae), gen. n. Paradoxus Millière, 1869 (Yponomeutidae), syn. n. of Kessleria Nowicki, 1864 Parahyponomeuta Toll, 1941 (Yponomeutidae), syn. n. of Kessleria Nowicki, 1864 Paraswammerdamia Friese, 1960 (Yponomeutidae), gen. n. Pseudocalantica Friese, 1960 (Yponomeutidae), gen. n. Pseudoswammerdamia Friese, 1960 (Yponomeutidae), gen. n. joannisella Maneval, 1934 (Zelleria), syn. n. of Zelleria hepariella Stainton, 1849 phillyrella Millière, 1867 (Zelleria), syn. n. of Zelleria hepariella Stainton, 1849